1970
DOI: 10.3126/hjs.v2i3.226
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of tree species in two community forests of Dolpa district, mid-west Nepal

Abstract: Two community forests, Amaldapani and Juphal from Dolpa district, were selected for a study of quantitative analysis of tree flora. A total of 419 individual trees representing 16 species, 16 genera and 11 families were recorded. Total stand density and basal area were, respectively, 2100 trees ha-1 and 90 m2ha-1 in Amaldapani and 2090 tree ha-1 and 152 m2ha-1 in Juphal. Of the families, the Pinaceae was the most diverse, with 28 individuals representing five species and five genera, followed by the Rosaceae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
6
24
1
Order By: Relevance
“…They revealed that the species with high tolerance to climatic variability had followed mid-domain model predictions, and showed a nonlinear relationship with temperature, whereas tropical species richness tracked temperature and area. The Shannon diversity values recorded (1.10 to 2.34) in our study lies close to the reported range of 1.16 to 3.40 for the Himalayan range (Pandey, 2001, Kunwar andSharma, 2004). Maximum value of evenness in Lower temperate zone represented homogeneous communities having similar species distribution.…”
Section: Tree Diversitysupporting
confidence: 66%
“…They revealed that the species with high tolerance to climatic variability had followed mid-domain model predictions, and showed a nonlinear relationship with temperature, whereas tropical species richness tracked temperature and area. The Shannon diversity values recorded (1.10 to 2.34) in our study lies close to the reported range of 1.16 to 3.40 for the Himalayan range (Pandey, 2001, Kunwar andSharma, 2004). Maximum value of evenness in Lower temperate zone represented homogeneous communities having similar species distribution.…”
Section: Tree Diversitysupporting
confidence: 66%
“…Shannon species diversity (H′) and concen tration of dominance (cd) of the present study sites are more or less similar to the val ues reported by Kunwar & Sharma (2004) in a comparative study between two com munity forests in Dolpa district of mid-west Nepal. These values were comparable with those reported for the Chir pine forest in Garhwal Himalaya (Bhandari et al 1998).…”
Section: Discussionsupporting
confidence: 88%
“…Valencia et al (1994) reported the density values between 716 to 1440 ha -1 for Kurupukari forest in Guyana and density of terra firm forest as 1561 ha -1 respectively. Kunwar & Sharma, (2004) carried out a study in Dolpa district of mid-west Nepal, where the density values reported from 2090 to 2100 ind ha -1 . In Kumaun Himalayan forests in Uttarakhand, Bargali et al (1987) The decrease in diversity and species richness at high elevation strata could be due to ecophysiological constraints, such as reduced growing season, low temperature and low productivity (Korner, 1998;Gairola et al, 2008).…”
Section: Forest Composition and Structurementioning
confidence: 99%